Survival Outcomes for Yttrium-90 Transarterial Radioembolization With and Without Sorafenib for Unresectable Hepatocellular Carcinoma Patients - Teyateeti, Ajalaya (J Hepatocell Carcinoma, 2020)
PURPOSE: To assess the overall survival (OS) and progression-free survival (PFS) of unresectable hepatocellular carcinoma (HCC) patients undergoing yttrium-90 glass–microsphere transarterial radioembolization (TARE) with and without concurrent sorafenib. METHODS: OS and PFS were analyzed in 55 patients with an intrahepatic tumor (IHT) ≤50% without advanced or aggressive disease features (ADFs), which was referred to presence of infiltrative/ill-defined HCC, macrovascular invasion, or extrahepatic disease treated with only TARE (TARE_alone) and in 74 patients with IHT ≤50% with ADFs or IHT >50% treated with TARE and sorafenib (TARE_sorafenib). Prognostic factors for OS and PFS were identified using univariate and multivariate analyses. RESULTS: Median OS and PFS of TARE_alone patients were 21.6 (95% CI 6.1–37.1) and 9.1(95% CI 5.2–13.0) months, respectively, and for TARE_sorafenib patients 12.4 (95% CI 9.1–15.6) and 5.1 (95% CI 2.6–7.5) months, respectively. Better OS was associated with serum AFP <400 (HR 0.27, p=0.02) in TARE_alone, and IHT ≤50% (HR 0.39, p=0.004) and AFP <400 (HR 0.5, p=0.027) in TARE_sorafenib. Unilobar involvement (HR 0.43, p=0.029) and AFP <400 ng/mL (HR 0.52, p=0.015) correlated with better PFS in TARE_alone and TARE_sorafenib, respectively. Adverse events (AEs) were more frequent in TARE_sorafenib than TARE_alone (92.4 vs 80.3%), but only 9.3% were grade 3 or higher AEs. CONCLUSION: TARE_alone provided the most prominent survival benefit in IHT ≤50%–without ADF patients who had unilobar HCC and serum AFP <400 ng/mL. TARE and sorafenib yielded the best outcomes in patients with IHT ≤50% and serum AFP <400 ng/mL, with some additional grade 1–2 AEs compared to TARE only.